2014
DOI: 10.1017/s1041610214000088
|View full text |Cite
|
Sign up to set email alerts
|

Participation of end users in the design of assistive technology for people with mild to severe cognitive problems; the European Rosetta project

Abstract: The user participatory design resulted in valuable input from persons with dementia, informal carers and professional carers/dementia experts, based on which a first prototype Rosetta system was built.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
128
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(129 citation statements)
references
References 22 publications
5
128
0
1
Order By: Relevance
“…In practice, however, people with dementia have rarely been involved in technology development, with user acceptability tending to be assessed via family carers and others [11,24,34]. Successful examples of collaborative working with people with mild-to-moderate dementia are emerging [14,33,35-37]. However, people with more severe dementia are less often included in development of assistive technologies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In practice, however, people with dementia have rarely been involved in technology development, with user acceptability tending to be assessed via family carers and others [11,24,34]. Successful examples of collaborative working with people with mild-to-moderate dementia are emerging [14,33,35-37]. However, people with more severe dementia are less often included in development of assistive technologies.…”
Section: Resultsmentioning
confidence: 99%
“…Usability issues: Little research so far has been conducted in community dementia care and support, with only a few studies exploring the usability of assistive technology in supporting everyday life [37,47,48]. The results showed that people with dementia were able to use the technology, but that additional support by informal caregivers or professionals was often needed.…”
Section: Discussionmentioning
confidence: 99%
“…In one case, a father became physically aggressive towards his daughter when she took his car key. Strang et al (2006), Meiland et al (2014), and Liken et al (2001) describe similar examples of safety issues resulting in carers deciding to take action because the situation had reached crisis point (Liken, 2001;Meiland et al, 2014;Strang, 2006). Reported examples of taking action to prevent harm included seeking professional advice, accessing services, and restricting or monitoring activity of the person with dementia.…”
Section: What Happens During Crisismentioning
confidence: 99%
“…Additional assistive technologies are also being directed toward persons with dementia themselves to help monitor the movements of individuals at night, alert caregivers to their need for help, and provide soothing music, images, or gentle cuing to return to bed [37][38][39]. Technological strategies that might help reduce the unpredictability of dealing with care-receivers at night could be particularly helpful as there is evidence that caregiver perceptions about the inconsistency in their sleep may have as much impact on caregiver mood and burden as the actual sleep quality itself [40].…”
Section: Caregiver Sleep Interventionsmentioning
confidence: 99%